Acute phase protein response and changes in lipoprotein particle size in dogs with systemic inflammatory response syndrome. (14th April 2022) - Behling‐Kelly, Erica; Haak, Carol E.; Carney, Patrick; Waffle, Jessica; Eaton, Kelly; Goggs, Robert
Abstract: Background: Improved methodology to measure acute phase proteins and determination of lipoprotein particle‐size distribution (PSD) could be clinically useful in dogs with systemic inflammatory processes. Objectives: Evaluate an immunoturbidometric assay for serum amyloid A (SAA) and lipoprotein PSD in dogs with sepsis, nonseptic systemic inflammation, and in healthy controls. Correlate dyslipidemic changes with SAA and C‐reactive protein (CRP) concentrations. Animals: Twenty‐five dogs with sepsis, 15 dogs with nonseptic systemic inflammation, and 22 healthy controls. Methods: Prospective, case‐control study. Variables included SAA, CRP, and electrophoretic subfractionation of high‐ and low‐density lipoproteins (HDL, LDL). Continuous variables were compared using ANOVA or Kruskal‐Wallis tests with linear regression or Spearman's rank correlation used to assess relationships between variables. Results: Median SAA and CRP concentrations were greater in dogs with sepsis (SAA 460 mg/L, interquartile range [IQR] 886 mg/L; CRP 133.2 mg/L, IQR 91.6 mg/L) and nonseptic inflammation (SAA 201 mg/L, IQR 436 mg/L; CRP 91.1 mg/L, IQR 88.6 mg/L) compared to healthy dogs (SAA 0.0 mg/L, IQR 0.0 mg/L; CRP 4.9 mg/L, IQR 0.0 mg/L) P  < .0001. A cutoff of >677.5 mg/L SAA was 43.2% sensitive and 92.3% specific for sepsis. Low‐density lipoprotein was higher in dogs with sepsis 29.6%, (mean, SD 14.6) compared to 14.4% (mean, SD 5.6) of all lipoproteins in healthy controls ( P  = .005). High‐density lipoprotein was not associated with CRP but was negatively correlated with SAA ( r s −0.47, P  < .0001). Subfractions of LDL and HDL differed between groups (all P  < .05). Conclusions and Clinical Importance: Measurement of SAA using the immunoturbidometric assay evaluated in this study and lipoprotein PSD in dogs with inflammation might help distinguish septic from nonseptic causes of inflammation.